Sensitivity and Specificity Assessment of Histopathology and GeneXpert in Diagnosing Extrapulmonary Tuberculosis at Gulab Devi Hospital, Lahore, Pakistan: A Retrospective Study: Sensitivity and Specificity in Diagnosing Extrapulmonary Tuberculosis - Mohsin, Rameesha; Ali, Maratab; Siddique, Mahwish; Zaheer, Mohsin; Ambreen, Atiqa; Khanum, Hamail (Pakistan Journal of Health Sciences, 2024)
Extrapulmonary Tuberculosis (EPTB), including Spinal Tuberculosis (STB), poses diagnostic challenges due to diverse clinical presentations and limitations of conventional diagnostic methods. Objective: To assess the sensitivity and specificity of Gene Xpert and histopathology in diagnosing EPTB at Gulab Devi Chest Hospital, Lahore, Pakistan. Methods: Data from patients diagnosed with EPTB between May 15th and October 15th, 2024, were analyzed. Gene Xpert and histopathology results were compared with Culture as the gold standard. Results: The study included 299 individuals, 61.2% of whom were females and 38.8% of whom were males. Gene Xpert demonstrated a sensitivity of 90.48% and specificity of 59.75%, while histopathology exhibited a sensitivity of 88.89% and specificity of 60.17%. Conclusion: Gene Xpert and histopathology were valuable tools for diagnosing EPTB, complementing traditional methods.